Landslide Hazards Induced by Heavy Rainfall in August 2021 in the Northern Part of the Aomori Prefecture, Japan - YAMAMOTO, Yusuke; KUDO, Yushi; KATO, Kiyokazu; MORI, Hiroshi; IWATA, Hideya; ARAI, Kenichi; KOGA, Yuki; TSUSHIMA, Misa; KUROIWA, Chie; KOBAYASHI, Motoshiko; ISHIKAWA, Takeaki; MIURA, Jun; et al. (International Journal of Erosion Control Engineering, 2022)
On August 10, 2021, a total of 454 landslides and debris flows in the northern part of the Shimokita Peninsula, Aomori, Japan, resulted in one of the major natural disasters in the region in recent years. Large amounts of rainfall of 385 mm fell on 9 and 10 August, due to low atmospheric pressure and the consequent Typhoon Lupit (No. 9) passing over the Sea of Japan. The event resulted in landslides, flooding, and damage to houses, roads, bridges, and carried large wood and debris into the rivers, which caused blockages at dam locations. Landslides occurred mainly in the fluvial dissected Koakakawa and Ohakakawa River Basins and on the steep slopes of costal terrace scarps nearby Yakeyamasaki. Landslides were primarily associated with weathered tuffaceous mudstone and weathered andesitic green-colored tuff in the Koakakawa and Ohakakawa Basins and weathered pyroclastic flow, colluvium, and gravel layers nearby the Yakeyamasaki. Pipping holes were observed within or at the bottom of weathered tuffaceous mudstone, weathered pyroclastic flow, and colluvium, suggesting the landslide occurrence may have been caused by the amount of groundwater present.